Effects of non-pharmacological methods on post-operative procedural pain management in neonates admitted in the neonatal intensive care unit: A systematic review - Sharma, Abhishek; Sharma, Nidhi; Chahal, Aksh (Paediatrica Indonesiana, 2024)
Background In the post-operative period during the NICU stay, neonates must undergo various painful procedures. Non-pharmacological methods may be beneficial in managing the harmful effects of procedural pain on the development of neonates in their early life. Objectives To investigate the effect of non-pharmacological methods on post-operative procedural pain in neonates admitted to neonatal intensive care units. Methods A search in electronic databases was done to identify randomized clinical trials published from 2010 to 2020 that encompassed neonates undergoing painful procedures in the NICU and followed PRISMA guidelines. Studies with non-human subjects, neonates with unstable vital signs, non-clinical studies, and incomplete methodology were excluded. PubMed, Cochrane, and Physiotherapy Evidence Database (PEDro) were evaluated respectively using Medical Subject Headings (MeSH) and Health Sciences Descriptors (DeCS). Results Two reviewers examined articles independently and found 11 articles that met the study's inclusion criteria, with a total of 955 neonates with non-pharmacological methods of pain management in neonates. Non-pharmacological methods, such as massage therapy, oral sucrose, kangaroo mother care, and facilitated tucking showed significant reduction in pain scores among neonates who underwent painful procedures in NICU. Outcomes showed variability in effectiveness, emphasizing the need for tailored approaches. Conclusions The findings indicated that non-pharmacological methods can effectively manage pain in neonates admitted to the NICU. Pain management improves the clinical condition of neonates and promotes parents-neonate bonding, with consequent reduction in length of stay in the hospital.